Surgery-first approach with 3D customized passive self-ligating brackets and 3D surgical planning: Case report - Juan Fernando Aristizábal; Rosana Martínez-Smit; Cristian Díaz; Valfrido Antonio Pereira Filho
ABSTRACT It is possible to unify three-dimensional customized orthodontic techniques and three-dimensional surgical technology. In this case report, it is introduced a treatment scheme consisting of passive self-ligation customized brackets and virtual surgical planning combined with the orthognathic surgery-first approach in a Class III malocclusion patient. Excellent facial and occlusal outcomes were obtained in a reduced treatment time of five months.